REFINERY OF CITRONELLA OIL USING VACUUM HYDRODISTILATION METHOD IN ACEH UTARA DISTRICT - S Syafruddin; Reza Fauzan; Zulfan Khairil Simbolon; Rizal Syahyadi; Atiqah Aida; Rima Dhinta Dewi Astuti; Isra Adelya Izzati; Pocut Nurul Alam (Politeknik Negeri Lhokseumawe, 2023)
Citronella oil is a non-timber forest product (NTFP) and is commercially obtained from the distillation of citronella leaves (Cymbopogon nardus L). Fragrant citronella leaves are one of the raw materials for obtaining vegetable oils in the form of essential oils. Essential oil is the main component consisting of composition in the form of geraniol and citronellal. The process of extracting essential oils can be done using various methods, one of which is the Vacuum Hydrodistillation method. The Vacuum Hydrodistillation method is carried out using a vacuum pump as a pressure guard and the boiling point of the distillation process does not exceed the boiling point temperature of water, which is 1000 C, so that the oil produced is maintained its purity. The vacuum hydrodistillation process of citronella was carried out for 3, 5, and 7 hours with each treatment using random and whole pieces of raw material. The resulting essential oil products were analyzed in the form of yield, density, refractive index and oil composition analysis using GC-MS. The best essential oil yields from citronella were obtained under operating conditions with random samples and distillation time of 5 hours. Where the yield produced is 0.17% with a refractive index of 1.41570 and a density of 0.92735 gr/ml.Â Keywords: Essential Oil, Vacuum Hydrodistillation, Fragrant Lemongrass, Geraniol